FORMATION OF NEW INDUSTRIAL SECTORS AS A FEATURE OF INDUSTRIAL AND TECHNICAL DEVELOPMENT OF MOSCOW IN THE LAST THIRD OF THE XIX – EARLY XX CENTURIES - A. A. Romanov; V. A. Kolobkova (Вестник университета)
The period of the late XIX – early XX centuries, which is characterized by the active development of capitalism in Russia and the emergence of a number of new industrial sectors, – has been considered. These processes were clearly manifested in Moscow, which had turned into the largest industrial center. The emergence of advanced technical industries has been shown: printing, chemical, electrical. The capitalist level of industrial development in Moscow at the beginning of the XXth century is evidenced by the processes of concentration, combination and monopolization of production in many industries. The products of Moscow enterprises were in demand both within the country and abroad. It has been shown that the Moscow factory industry acted as a conductor of the latest technology, not only for a vast area of central provinces, but also for all Russia.